PENGENDALIAN KUALITAS DENGAN PENDEKATAN STATISTICAL QUALITY CONTROL (SQC) PADA ROTI RIZKY KENDARI - Usman Usman (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
This study aims to determine the quality control of bread in Roti Rizky kendari with the Statistical Quality Control approach. The data used are primary data and secondary data obtained by conducting direct observations of various processes carried out starting from the raw material to the final product. The analytical method used is Statistical Quality Control with four approaches namely inspection sheet, control chart, pareto diagram, and causal diagram.The results of this study indicate that the quality control carried out on bread production in Roti Rizky Kendari's business is still not effective, because there are still products that exceed the tolerance limit set by Roti Rizky which is 5% and from the results of the research the type of disability that occurs is gross defects of 271 packets or 1.74%, charred/charred defects of 382 packets or 2.45%, and outgoing defects of 459 packets or 2.94% and total defects totaling 1,112 or 7.13. From the calculation of the overall Control Chart the number of defective breads in November 2018 is not outside the upper control limit (UCL) as well as for those at the lower control limit (LCL). From the Pareto diagram analysis the most dominant type of disability occurs because the contents come out which is as much as 459 or 41.28%. The results of the causal diagram research are the factors that are the main causes of disability caused by human factors, machines and methods.